Oral amoxicillin and amoxicillin–clavulanic acid: properties, indications and usage. (July 2020) - Huttner, A.; Bielicki, J.; Clements, M.N.; Frimodt-Møller, N.; Muller, A.E.; Paccaud, J.-P.; Mouton, J.W.
Abstract: Background: Amoxicillin has been in use since the 1970s; it is the most widely used penicillin both alone and in combination with the β-lactamase clavulanic acid. Objectives: In this narrative review, we re-examine the properties of oral amoxicillin and clavulanic acid and provide guidance on their use, with emphasis on the preferred use of amoxicillin alone. Sources: Published medical literature (MEDLINE database via Pubmed). Content: While amoxicillin and clavulanic acid have similar half-lives, clavulanic acid is more protein bound and even less heat stable than amoxicillin, with primarily hepatic metabolism. It is also more strongly associated with gastrointestinal side effects, including Clostridium difficile infection, and, thus, in oral combination formulations, limits the maximum daily dose of amoxicillin that can be given. The first ratio for an amoxicillin–clavulanic acid combination was set at 4:1 due to clavulanic acid's high affinity for β-lactamases; ratios of 2:1, 7:1, 14:1 and 16:1 are currently available in various regions. Comparative effectiveness data for the different ratios are scarce. Amoxicillin–clavulanic acid is often used as empiric therapy for many of the World Health Organization's Priority Infectious Syndromes in adults and children, leading to extensive consumption, when some of these syndromes could be handled with a delayed antibiotic prescription approach or amoxicillin alone. Implications: Using available epidemiological and pharmacokinetic data, we provide guidance on indications for amoxicillin versus amoxicillin–clavulanic acid and on optimal oral administration, including choice of combination ratio. More data are needed, particularly on heat stability, pharmacodynamic effects and emergence of resistance in 'real-world' clinical settings.